The Black Sea and NATO in the Age of Access-Denial - Taylor, Francis; Manea, Octavian (Studia Politica (Bucuresti), 2018)
The article explores the implications of the rise of Russian anti-access/area-denial (A2/AD) capabilities for NATO’s Eastern Frontier, especially the broader Black Sea region. The reality is indicative of a broader global trend where assertive revisionist powers are not only questioning the post-1989 rules-based international order but are also developing the antidotes to the so-called American Way of War, one that largely shapes the NATO operational profile. This type of ecosystem is at the forefront of what Russia has been doing over the past few years in Kaliningrad and Crimea - developing concepts of operations, especially the A2/AD component, that challenge NATO’s way of reassuring its frontline allies. The problem is that the NATO caucus in the Black Sea remains highly fragmented in its threat perception. Increasingly close economic and political ties to Russia combined with diplomatic discord concerning the US and NATO makes Turkey a less reliable ally. Meanwhile, Bulgaria’s long tradition of close cultural and economic ties to Russia remains concerning. At the same time, NATO needs to do more. The West must understand that its smaller allies don’t have the luxury of time or economic power and must adapt its approach accordingly to credibly reassure its Black Sea allies.